Psychological Analysis of Literary Texts - مەولود ئیبراهیم حەسەن; سازان جوهر حمە غریب (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The study of psychoanalysis of literature and psychological criticism is an important step in understanding the basic principles of the emergence of the psychoanalysis school within psychology, because this school relied on analysis of the literary texts to formulate its basic principles and views and was able to derive from this analysis a set of psychological concepts and terms. This paper deals with a precise study of how literary psychoanalysis develops and how to construct a psychoanalytic approach to literature. For a deeper understanding of the principles of this critique based on psychological analysis in literature, it presents the critical issues of the psychoanalytic approach to literature, especially those related to the relationship of the creator and the impact of psychological aspect and environment of creativity on creating the literary text and its manifestations on the text and the reader, as well as other important topics related to the text.